El diseño del currículo y el modelo pedagógico en la formación por ciclos en áreas de la tecnología - Jirón Popova, Mirna (Revista Científica, 2012)
This paper present the results from the research project on Design of Curricular and Pedagogical Models for the education of Technicians, Technologists, and Engineers under the modality of cycles, carried out by investigators of the Group or Research in Technological Education throuhg Cycles - GIDETCI (because of its meaning in Spanish) which belongs to the Faculty of Technology of the District’s University: Universidad Distrital Francisco José de Caldas. The study intended to obtain knowledge of current curriculum design and pedagogical aspects of education the Technicians, Technologists, and Engineers under the modality of propaedeutic cycles. The results suggest that the design of curricula do not require a particular curriculum theory and that the formation of technological knowledge should be based to the solution of problems.